Kolicestvennaja ocenka sinusovoj aritmii posle fiziceskoj nagruzki s ispol'zovaniem avtokorreljacionnogo analiza - Zobkov, V. V. (Teorija i Praktika fiziceskoj Kul'tury, 2005)
In the work the quantitative analysis of sinus arrhythmia on autocorrelogram of cardio intervals at rest and after realization of functional tests with muscular loading at healthy students was carried out.